Critical degradation of Peruvian Plantcutter Phytotoma raimondii habitat in Lobitos, Talara - Flanagan, Jeremy N. M. (2020)
The threatened Peruvian Plantcutter Phytotoma raimondii is a restricted-range species, endemic to the north coast of Peru. As a specialist herbivore, it is only found at sites with an adequate diversity of xerophytic flora. Although it is recognized that the species is under threat from habitat degradation and loss, little or no attempt has been made to measure these changes. This study catalogues the floral diversity and degradation of sites near Lobitos town, north of Talara, to determine the loss of this species´ habitat. Fieldwork was conducted between November 2019 and January 2020. All larger plants (with a diameter ≥ 5 cm near ground level) and all deforested Prosopis pallida (Algarrobo) stumps were georeferenced over a 10 ha plot at the main site of Cerro Blanco, c. 2 km south of Lobitos. The height, width and general health of each bush were noted, and the diameter of P. pallida stumps measured. Additionally, two smaller comparative plots, (0.3 and 0.75 ha) were surveyed c. 2.5 km to the north of Lobitos. Results point to an alarming and accelerated rate of degradation of this habitat type due to the deforestation and dieback of P. pallida: a key species in this habitat and important food source for the Plantcutter. Removal of P. pallida appears to affect the stability of sites, with other important species, e.g. Lycium boerhaviifolium (Palo Negro) dying off after logging. Without urgent remedial action, the Peruvian Plantcutter´s habitat will continue to become ever scarcer and more fragmented.